EVALUATION OF WETLAND PLANTS TREATMENT POTENTIALS FOR ACID MINE DRAINAGE IN TANZANIA (Nigerian Journal of Technology, 2024)
Acid mine drainage occurs when sulfide minerals in mining activities come into contact with water and air, generating water with a low pH, high levels of sulfate, and metals. Treating acid mine drainage is a major challenge in gold mining operations worldwide and can be very costly. This study aims to screen and experimentally test potential local wetland plants for acid mine drainage treatment. Selected wetland plants were tested in a 12-liter plastic container, simulating a wetland treatment. The results of this study revealed that four out of six plants survived under acid mine drainage conditions. These plants included Cyperus imbricatus, Pennisetum purpureum, Typha latifolia, and Phragmites mauritianus,which all showed survival over the 63 days of experimental monitoring. The remaining two plants, Ipomea aquatica and water lotus (Nymphaeaceae), died within seven days of the experiment. The surviving plants were able to increase the pH from 3.2 to 7.1 and lower the levels of sulfate and metals in the acid mine drainage water. Furthermore, these four plants were able to improve the water quality by more than 94%, reducing heavy metal levels significantly (Mn from 53 to 1 mg/L, Ni from 2.4 to 0.3 mg/L, and Fe from 2.3 to 0.03 mg/L). This study suggests that selected local wetland plants have the potential to be a sustainable technology for treating acid mine drainage water.